Mesenchymal Stromal Cells as Potential Antimicrobial for Veterinary Use—A Comprehensive Review - Russell, Keith A.; Garbin, Livia C.; Wong, Jonathan M.; Koch, Thomas G. (Frontiers in Microbiology, 2020)
The emergence of "superbugs" resistant to antimicrobial medications threatens populations both veterinary and human. The current crisis has come about from the widespread use of the limited number of antimicrobials available in the treatment of livestock, companion animal, and human patients. A different approach must be sought to find alternatives to or enhancements of present conventional antimicrobials. Mesenchymal stromal cells (MSC) have antimicrobial properties that may help solve this problem. In the first part of the review, we explore the various mechanisms at work across species that help explain how MSCs influence microbial survival. We then discuss the findings of recent equine, canine, and bovine studies examining MSC antimicrobial properties in which MSCs are found to have significant effects on a variety of bacterial species either alone or in combination with antibiotics. Finally, information on the influence that various antimicrobials may have on MSC function is reviewed. MSCs exert their effect directly through the secretion of various bioactive factors or indirectly through the recruitment and activation of host immune cells. MSCs may soon become a valuable tool for veterinarians treating antimicrobial resistant infections. However, a great deal of work remains for the development of optimal MSC production conditions and testing for efficacy on different indications and species.